Unraveling the genomic architecture of supernumerary (iso-)dicentric chromosomes in Dup15q syndrome: insight from a systematic literature-based study - Burkart, Sebastian; Ries, Markus; Romero, Verena; Burau, Karin; Schaaf, Christian P.; Hempel, Maja (American journal of medical genetics, 2025)
Chromosomal aberrations, particularly copy-number variations (CNVs), are prevalent in neurodevelopmental disorders (NDD) and significantly contribute to their pathogenesis. Copy-number gains (CN gains) in 15q11-q13, primarily consisting of a pseudo (iso-)dicentric chromosome 15 [ (i)dic(15) ] or an interstitial duplication, are among the most frequent CNVs in NDD. The associated Dup15q syndrome is an early onset neurodevelopmental disorder characterized by global developmental delay, behavioral issues, and seizures with a variable onset and expression of symptoms. While a correlation between number of 15q11-q13 CN gain and symptom severity has been proposed, it fails to fully explain the wide phenotypic variability observed. We conducted a comprehensive systematic literature-based analysis of the supernumerary (i)dic(15), generating the largest literature-based cohort consisting of patient-level genotype data for Dup15q syndrome to date. Our findings identified symmetric BP3:BP3 and asymmetric BP4:BP5 (i)dic(15) configurations as the most common (i)dic(15) formations, likely arising from distinct mechanisms and potentially driving characteristic genotype-phenotype outcomes. Additionally, we identified a significant gap within the molecular characterization of (i)dic(15), particularly regarding information on nucleotide-level breakpoint, genomic structure, and differentially imprinted genes, being important aspects for genotype-phenotype predictions. Our findings provide critical insight into the molecular architecture of (i)dic(15), offering valuable implications for understanding pathomechanisms and guidance for future research into the molecular and clinical aspects of Dup15q syndrome.
Gesehen am 29.07.2025